Pharmacy students' perceptions on environmental sustainability in pharmacy education and practice - Esa Y.H. Chen; Catherine Forrester; Aisling M. McEvoy; Judith Singleton (Elsevier, 2023)
Background: Given the negative environmental impacts of pharmaceuticals, including their contribution to healthcare's carbon footprint, pharmacists have a role in responding to the climate and biodiversity crises. Knowledge and education are required to support transitions to environmentally sustainable pharmacy practice (ESPP). The aim of this study was to explore Australian undergraduate pharmacy students' knowledge and attitudes towards environmental sustainability and ESPP curriculum content. Methods: Participants were surveyed using an anonymous online questionnaire deployed using Qualtrics. The questionnaire comprised of two main sections: the 15-item New Ecological Paradigm (NEP) scale to determine participants' environmental attitude score, and section on students' perceptions and curricular experience of environmentally sustainable practice which was adapted from previously published surveys. The invitation with survey link was disseminated via social media, Australian pharmacy student organisations, and direct approach. Quantitative data were reported descriptively. Qualitative data from responses to open-ended questions were analysed thematically using a reflexive, recursive approach. Incomplete survey responses were excluded from the analysis. Results: Of the 164 complete responses, 99% had previously received information on environmental sustainability. However, only 10% were knowledgeable about ESPP and only 8.5% were aware of ESPP content in their pharmacy school curriculum. Importantly, 70% of respondents saw ESPP as relevant to their future pharmacy practice, and 94% believed the pharmacy profession has a responsibility to undertake sustainability initiatives in the delivery of pharmaceutical care. Conclusions: Australian pharmacy students lacked knowledge of ESPP and few reported having curricular exposure to ESPP content in their pharmacy degrees. Therefore, ESPP content is an important area for development in pharmacy curricula.